2015
DOI: 10.1017/s0029665115000804
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into anti-epileptic effect and mechanisms of Ganoderma lucidum polysaccharides in in vivo and in vitro models

Abstract: There are about 60 million epileptic patients worldwide. Finding a more effective antiepileptic drug with fewer side effects is of continuing importance (1) . Ganoderma lucidum, a mushroom having been used as Traditional Chinese Medicine, has showed the effect of antiepileptic effect with no side-effects (2) . The aim of the present study was to assess the mechanisms of antiepileptic effects by Ganoderma lucidum polysaccharides (GLP).In study 1, effect of GLP on calcium turnover, Ca 2+ /calmodulin-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Several extracts of Ganoderma lucidum showed amelioration in this progress in a review [50], e.g., one study [51] showed that proteoglycan isolated from Ganoderma lucidum fruiting bodies shows protection renal morphology in diabetic mice in a dosedependently (75, 250, and 450 mg/kg) manner during a 8week treatment. According to previous research, the mechanism appears also via directly elimination reactive oxygen species, suppresses lipid peroxidation, and indirectly scavenges the radicals via activating antioxidant enzyme systems and chelation with metal ion by forming crossbridge between carboxyl groups decreasing reactive oxygen species generation [52][53][54][55][56][57][58][59][60]. This study showed that the expressions of the inflammatory factors IL-6, IL-1β, and TNF-α in the diabetic group were significantly increased, while they were reduced significantly after GLP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several extracts of Ganoderma lucidum showed amelioration in this progress in a review [50], e.g., one study [51] showed that proteoglycan isolated from Ganoderma lucidum fruiting bodies shows protection renal morphology in diabetic mice in a dosedependently (75, 250, and 450 mg/kg) manner during a 8week treatment. According to previous research, the mechanism appears also via directly elimination reactive oxygen species, suppresses lipid peroxidation, and indirectly scavenges the radicals via activating antioxidant enzyme systems and chelation with metal ion by forming crossbridge between carboxyl groups decreasing reactive oxygen species generation [52][53][54][55][56][57][58][59][60]. This study showed that the expressions of the inflammatory factors IL-6, IL-1β, and TNF-α in the diabetic group were significantly increased, while they were reduced significantly after GLP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin-Eosin (H&E) Staining. The rat brain tissues fixed with 4% paraformaldehyde were cut into 4 μm sections and stained with H&E as described previously [42], and the histological structure was observed using a 400x microscope (Nikon ECLIPSE Ni, Japan). Damaged neurons from 6 observed optical fields per rat were counted and used for the statistical analysis among groups.…”
Section: Animal Experimental Designmentioning
confidence: 99%
“…In addition, a variety of chemical interventions, including excitatory amino acids such as glutamate, N -methyl- d -aspartate (NMDA) and kainic acid; neurotoxins such as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and 6-hydroxydopamine (6-OHDA); and ageing-promoting agents such as d -galactose, are also shown to induce neurodegenerative symptoms via oxidative and inflammatory stresses [ 83 , 99 , 100 ]. As oxidative stress plays a pivotal role in neurodegeneration, antioxidant strategies, including food-derived antioxidant polysaccharides, are shown to attenuate neuronal damage and improve cognitive and motor functions in a range of neurodegenerative models ( Table 2 ) [ 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142...…”
Section: Alleviation Of Neurodegeneration By Food-derived Antioxidmentioning
confidence: 99%
“…For instance, L. barbarum polysaccharide can increase cell viability and suppress JNK activation in glutamate-exposed rat primary cortical neurons [ 129 ], suggesting an involvement of MAPK pathway in the neuroprotective effect of the polysaccharide. Another example is G. lucidum polysaccharide, which is shown to alleviate epileptic symptoms and up-regulate the expression of calcium/calmodulin-dependent protein kinase II, a kinase that plays an important role in calcium transfer in neurons, in kainic acid-injected rats [ 123 ]. As calcium overload mediates excitatory amino acid-induced neurotoxicity [ 164 ], prevention of calcium transporting may contribute to this neuroprotective effect of G. lucidum polysaccharide.…”
Section: Alleviation Of Neurodegeneration By Food-derived Antioxidmentioning
confidence: 99%